Camel milk protectiveness toward multiple liver disorders: A review - Shakeel, Khunsha; Rabail, Roshina; Iahtisham-Ul-Haq,; Sehar, Sabrina; Nawaz, Asad; Manzoor, Muhammad Faisal; Walayat, Noman; Socol, Claudia Terezia; Maerescu, Cristina Maria; Aadil, Rana Muhammad (Frontiers in Nutrition, 2022)
Camel milk is known as the white gold of the desert because it contains a variety of nutrients in it which play a key role in the human diet. The health benefits of camel milk have been described in a variety of diseases such as diabetes, kidney disease, Autism, hepatitis, etc. including improved overall survival. It causes a major health burden of liver diseases worldwide, and the ninth leading cause of death is due to liver cirrhosis in Western countries. The treatment is mostly not effective for cirrhosis, fatty liver, and chronic hepatitis which are the most common diseases of the liver, carry the risk of side effects, and are often extremely expensive, particularly in the developing world. A systematic review of studies was performed to determine the association of consumption of camel milk on multiple diseases of the liver. The impact of camel milk on the laboratory tests related to the liver disorder, viral hepatitis, nonalcoholic fatty liver disease (NAFLD), cirrhosis, and hepatocellular carcinoma (HCC) were evaluated. The consumption of camel milk was ac-companied to modulate the values of serum gamma-glutamyl transferase, aspartate aminotransferase, and alanine aminotransferase in the persons who are at the risk of liver disease. In the patients with chronic liver disease, it was observed that they have low rates of mortality and low chances of progression to cirrhosis when they consume camel milk. Therefore, in patients with liver diseases, the addition of camel milk into their normal daily diet plan should be encouraged. In this review, camel milk's impact on the different kinds of liver diseases or any disorder associated with liver functioning was evaluated. The camel milk has a therapeutic as well as a preventive role in the maintenance and improving the metabolic regulations of the body.